Neuroenhancement or Neurocheating? Rethinking Ethics in the Age of Cognitive Upgrades - Correia de Barros, Eugénia (Journal of NeuroPhilosophy, 2025)
In its widest definition, neuroenhancement describes actions done by healthy people to enhance their mental abilities beyond what is naturally possible. In contrast to therapy, which tries to reverse disease or lessen suffering, enhancement seeks to increase a person's potential regardless of disease or suffering. On the other hand, the growing application of neuromodulation technologies presents serious moral questions about social interaction and the pursuit of personal traits. Therefore, this paper aims to convince the scientific community that neuroenhancement has been used since the beginning of human civilization, whether through tools, inventions, or modern technologies. As such, it should be viewed as an extension of the innate human desire to innovate and improve.